In Vitro Seed Germination in Withania somnifera L. (Dunal): A High-value Medicinal Plant - Thapa, Chandra Bahadur; Singh, Anata Gopal; Gyawali, Shanti Devi (Himalayan Biodiversity, 2025)
Withania somnifera L. (Dunal) is a valuable medicinal plant utilized in traditional medicine, Ayurveda, Unani, and traditional Chinese medicine to cure various disorders and diseases. This study aims to evaluate the percentage of in vitro seed germination in Murashige and Skoog (MS) media in the absence of plant growth regulators (PGRs) and supplemented with the α-naphthalene acetic acid (NAA) and benzylaminopurine (BAP). Seeds were cultured on quarter-, half-, and full-strength MS media (control treatment), in addition to quarter-, half-, and full-strength MS media supplemented with 0.5-1.5 mg/L NAA + 0.5-2.0 mg/L BAP (treatment with PGRs). The control treatment had a higher percentage of seed germination than the PGR treatment. In the case of control treatment, the maximum seed germination rate (80%) was found in quarter-strength (¼) of MS, followed by half- (1/2) and full-strength MS media. Similarly, in the case of treatment with PGRs, the maximum percentage (67%) of seed germination was found in quarter-strength (¼) of MS media supplemented with 0.5 mg/L NAA + 1.5 mg/L BAP as compared to other combinations. Seed germination occurred faster (after 3 weeks of culture) in the control treatment than in the PGR treatments (after 5 weeks). This research will be valuable for the production of sterile explants for the micropropagation of W. somnifera in a short time, and it might be useful for both ex-situ conservation and germplasm conservation of this species.